Muscle layer histopathology and manometry pattern of primary esophageal motility disorders including achalasia. Issue 3 (3rd October 2016) - Nakajima, N.; Sato, H.; Takahashi, K.; Hasegawa, G.; Mizuno, K.; Hashimoto, S.; Sato, Y.; Terai, S.
Abstract: Background: Histopathology of muscularis externa in primary esophageal motility disorders has been characterized previously. We aimed to correlate the results of high‐resolution manometry with those of histopathology. Methods: During peroral endoscopic myotomy, peroral esophageal muscle biopsy was performed in patients with primary esophageal motility disorders. Immunohistochemical staining for c‐kit was performed to assess the interstitial cells of Cajal (ICCs). Hematoxylin Eosin and Azan‐Mallory staining were used to detect muscle atrophy, inflammation, and fibrosis, respectively. Key Results: Slides from 30 patients with the following motility disorders were analyzed: achalasia (type I: 14, type II: 5, type III: 3), one diffuse esophageal spasm (DES), two outflow obstruction (OO), four jackhammer esophagus (JE), and one nutcracker esophagus (NE). ICCs were preserved in high numbers in type III achalasia ( n =9.4±1.2 cells/high power field [HPF]), compared to types I ( n =3.7±0.3 cells/HPF) and II ( n =3.5±1.0 cells/HPF). Moreover, severe fibrosis was only observed in type I achalasia and not in other types of achalasia, OO, or DES. Four of five patients with JE and NE had severe inflammation with eosinophilic infiltration of the esophageal muscle layer (73.8±50.3 eosinophils/HPF) with no epithelial eosinophils. One patient with JE showed a visceral myopathy pattern. Conclusions & Inferences: Compared to types I and II, type III achalasia showed preserved ICCs, with variable data regarding DES and OO. In disorders considered as primary esophageal motility disorders, a disease category exists, which shows eosinophilic infiltration in the esophageal muscle layer with no eosinophils in the epithelium. Abstract : We aimed to analyze the relation between high‐resolution manometry (HRM) findings and histopathology of muscularis externa in esophageal motility disorders. ICCs were preserved in high numbers in type III achalasia compared to other achalasia types. In some patients with JE and NE, eosinophilic infiltration of the esophageal muscle layer was shown, possibly related to the hypercontraction on HRM. Histopathological examination of the muscle layer in esophageal motility disorders may elucidate the pathology.